Effect of E-WoHealth on Perceived Body Image, Self Confidence, and Body Mass Index (BMI) among Female Adolescents - Rizkiati Nurdin; Saidah Syamsuddin; Yusring Sanusi Baso; Andi Wardihan Sinrang; Werna Nontji; Deviana Soraya Riu (Poltekkes Kemenkes Palu, 2023)
Low acceptance of body image can lead to behavioral changes and disorders such as depression, excessive desire to lose weight and dieting, eating disorders, as well as low self-esteem. This study aims to analyze the effect of using E-WoHealth on perceived body image, self-confidence, and Body Mass Index (BMI) among female adolescents. This study has obtained ethical approval issued by the Faculty of Public Health, Hasanuddin University No.105/UN4.14.1/YP.01.02/2023 3.01.2023. This was a Quasi-Experimental quantitative study with the R&D (Research and Development) approach and two-group Pre-test-Post-test design. The current study was conducted at State SHS 4 of Palopo City from February 20 to March 30, 2023. A sample size consisted of 108 students, who were selected through a total sampling technique and were assigned into 2 groups, namely the intervention group and the control group consisted of 54 respondents, respectively. The study design developed and validated learning media called Education Woman Health, later abbreviated as E-WoHealth, as a website containing animated videos, text videos and e-booklets to be applied as educational media. The study findings indicated a significant increase in the post-test perceptions of respondents with a p-value of 0.000 <0.05, which means there are differences in perceptions of female adolescents after being given education using E-WoHealth. Furthermore, there was a significant difference between the intervention group and the control group with a p-value 0.000 <0.05. It can be concluded that there was an effect of using web-based E-WoHealth on perceived body image, self-confidence and body mass index among female adolescents. Animated videos and e-booklets can be used as alternative educational medium to increase adolescents' perceptions for self-assessment to create self-confidence and a positive body image.